EDEMA PULMONAR POR SOBRECARGA DE FLUIDOTERAPIA - Conrado, Jayne Cristina; Salvagni, Ana Maria; Lusa, Fabrieli Tatiane; Pinheiro, Fernanda; Festugatto, Rafael; Vaccarin, Charline Vanessa (Anais de Medicina Veterinária, 2022)
.